Exploring Virulence Determinants of Filamentous Fungal Pathogens through Interactions with Soil Amoebae - Novohradská, Silvia; Ferling, Iuliia; Hillmann, Falk (Frontiers in Cellular and Infection Microbiology, 2017)
Infections with filamentous fungi are common to all animals, but attention is rising especially due to the increasing incidence and high mortality rates observed in immunocompromised human individuals. Here, Aspergillus fumigatus and other members of its genus are the leading causative agents. Attributes like their saprophytic life-style in various ecological niches coupled to nutritional flexibility and a broad host range have fostered the hypothesis that environmental predators, could have been the actual target for some of their virulence determinants. In this mini review, we have merged the recent findings focused on the potential dual-use of fungal defense strategies against innate immune cells and soil amoebae as natural phagocytes. Well-established virulence attributes like the melanized surface of fungal conidia or their capacity to produce toxic secondary metabolites have also been found to be protective against the model amoeba Dictyostelium discoideum. Some of the recent advances during interaction studies with human cells have further promoted the adaptation of other amoeba infection models, including the wide-spread generalist Acanthamoeba castellanii, or less prominent representatives like Vermamoeba vermiformis. We further highlight prospects and limits of these natural phagocyte models with regard to the infection biology of filamentous fungi and in comparison to the phagocytes of the innate immune system.